Surrounded by violence: how do individual perceptions and community context shape views about violence? - Sargeant, Elise (The Australian and New Zealand journal of criminology, 2018)
In this paper we examine the community- and individual-level characteristics associated with individuals’ perceptions of violence. We use data collected in the Australian Community Capacity Study Wave 3 survey of over 4000 individuals living in 148 local residential communities in Brisbane and employ multilevel models to examine the association between community context, individual perceptions of police effectiveness and the belief that people in one’s community support violence to resolve conflict. We find communities with histories of violent crime and more negative views about police effectiveness tend to be communities where residents perceive their neighbours will support the use of violence to resolve conflict.